Zad. 8. Doprowadź wyrażenie do najprostszej postaci i oblicz jego wartość liczbową
7(2a + 3)(a + 5) – 4a(a + 1) , dla a = –10​


Odpowiedź :

Odpowiedź:

7(2a + 3)(a + 5) – 4a(a + 1) =

=(14a+21)(a+5)-4a^2-4=

=14a^2+70a+21a+105-4a^2-4=

=10a^2+91a+101=10*(-10)^2+91*(-10)+101=1000-910+101=191

Szczegółowe wyjaśnienie:

Odpowiedź:

7 (2a + 3) (a + 5) - 4a (a + 1) = 14a²+ 70a + 21a + 105 - 4a² - 4 =

= 10a² + 91a + 101 = 10 * (- 10)² + 91 * (- 10) + 101 =

= 10 * 100 - 910 + 101 = 1000 - 910 + 101 = 191

Szczegółowe wyjaśnienie: